The Role of Proficiency in Kashmiri Language in Phonological Processing Skills: A Cognitive-linguistic Approach - Ahmad Mir, Farooq; Khan , Azizuddin (East European Journal of Psycholinguistics, 2022)
Language reflects the general aspects of human cognition and it works in terms of generalities, i.e. in terms of categories (Cruse, 2000). So, any of the linguistic expressions, whether it’s a phone, word, syllable or a sentence ends up in the representation of a category referring to a something that is usually aimed at sufficing the need for communication. These categories are conceptual or can be referred to as the abstract mental constructs. However, language is not an autonomous cognitive faculty which implies that language is not exactly an innate cognitive module and is not separated from non-linguistic cognitive abilities (Craft & Cruse, 2004). This study reports on the role of proficiency of Kashmiri language in phonological processing of illiterate native Kashmiri speakers. A total number 40 participants (20 Literate; 20 Illiterate), divided into two groups; were tested for Lexical Decision, Random Automatized Naming, Initial Phoneme Deletion, and Final Phoneme Deletion. The results suggested that the performance of both the groups was affected by Literacy and Proficiency in their native language i.e. Kashmiri. The effect of literacy on phonological processing was in consistence with the available literature however, the performance by illiterates was not worked out. This study attempted to find out the reasons for the performance of illiterates, and it was found that the illiterates can perform almost similar to those of literates on phonological awareness tasks because the proficiency in their native language enhances their phonemic and phonological awareness skills. Hence, the proficiency in Kashmir language has a role in phonological processing of illiterates.